Prediction of lesion-based response to PRRT using baseline somatostatin receptor PET - Aouf, Anas; Speicher, Tilman; Blickle, Arne; Bastian, Moritz B.; Burgard, Caroline; Rosar, Florian; Ezziddin, Samer; Sabet, Amir (Frontiers in Medicine, 2025)
AimThe heterogeneous expression of somatostatin receptors in gastroenteropancreatic neuroendocrine tumors (GEP-NET) leads to significant intra-individual variability in tracer uptake during pre-therapeutic [68Ga]Ga-DOTATOC PET/CT for patients receiving peptide receptor radionuclide therapy (PRRT). This study aims to evaluate the lesion-based relationship between receptor-mediated tracer uptake and the functional response to PRRT.MethodsA retrospective analysis was conducted on 32 patients with metastatic GEP-NET (12 pancreatic and 20 non-pancreatic), all treated with [177Lu]Lu-octreotate (4 cycles, with a mean of 7.9 GBq per cycle). [68Ga]Ga-DOTATOC PET/CT was performed at baseline and 3 months after the final PRRT cycle. Tumor uptake was quantified using the standardized uptake value (SUV). For each patient, 2 to 3 well-delineated tumor lesions were selected as target lesions. SUVmax, SUVmean (automated segmentation with a 50% SUVmax threshold), and corresponding tumor-to-liver ratios (SUVmaxT/L and SUVmeanT/L) were calculated. Functional tumor response was assessed based on the relative change in metabolic tumor volume (%ΔTVPET). The correlation between baseline SUV parameters and lesion-based functional response was analyzed using Spearman’s rank correlation.ResultsA total of 71 lesions were included in the analysis. The mean baseline SUVmax and SUVmean were 28.1 ± 15.9 and 13.6 ± 5.1, respectively. Three months after PRRT completion, the mean %ΔTVPET was 39.6 ± 52.1%. Baseline SUVmax and SUVmean demonstrated a poor correlation with lesion-based response (p = 0.706 and p = 0.071, respectively). In contrast, SUVmaxT/L and SUVmeanT/L were significantly correlated with lesion-based response (SUVmeanT/L: p = 0.011, r = 0.412; SUVmaxT/L: p = 0.004, r = 0.434). Among patient characteristics—including primary tumor origin, baseline tumor volume, and metastatic sites—only pancreatic origin was significantly associated with functional tumor volume reduction (ΔTVPET%: 56.8 ± 39.8 in pancreatic vs. 28.4 ± 50.1 in non-pancreatic NET; p = 0.020).ConclusionThe lesion-based molecular response to PRRT correlates with pretreatment somatostatin receptor PET uptake, particularly when expressed as tumor-to-liver SUV ratios (SUVmaxT/L and SUVmeanT/L).